Trapezoid Fracture Associated with Scaphoid Fracture in a Football Goalkeeper - Tetsuya Yamamoto; Takehiko Matsushita; Kenjiro Ito; Shinji Matsushima; Kazuya Yoshida; Ryosuke Kuroda (Case Reports in Orthopedics)
Introduction. Trapezoid fractures are uncommon in sports. We presented a rare case of a trapezoid fracture associated with a scaphoid fracture caused by punching a ball in a football goalkeeper. Case Presentation. A 19-year-old male who played as a football goalkeeper visited our hospital with complaints of sustained pain from the right wrist to the hand after punching a ball. Scaphoid fracture was diagnosed on plain radiographs, whereas trapezoid fracture was overlooked. Computed tomography revealed a displaced trapezoid fracture associated with a scaphoid fracture. Both fractures were successfully treated by open reduction and internal fixation using cannulated screws. Almost complete bone union was achieved at 5 months after surgery. The patient returned to play as a football goalkeeper. Conclusion. The simultaneous occurrence of trapezoid and scaphoid fractures has never been reported. Trapezoid fractures are rare and can be overlooked on plain radiographs, as what happened in the present case, because the trapezoid is small and overlaps with other carpal bones on plain radiographs. If there is sustained pain in the wrist and hand after punching, combined trapezoid and scaphoid fractures should be considered as the possible injury.